Translingualism in Three University Roles: Pedagogical Postures and Critical Cautions - Bennett, Cole (Journal of Academic Writing, 2020)
This paper offers and develops some useful parameters toward the ongoing conversations on multilingual and multidialectal writing students in Europe and the United States, two settings which produce oft-competing views of writers’ varied language backgrounds. I present a synchronic snapshot of writing pedagogy as it relates to translingualism at this temporal moment. Specifically, I seek to link three different university roles – classroom teachers, writing center directors, and writing across the curriculum (WAC) directors – to certain translingual postures and their consequential applications. By introducing and elaborating upon the labels Traditionalist, Allied Enthusiast, and Active Advocate as they attend each role, I wish to offer helpful ways to understand the consequences of embracing these postures. This charting of stakeholders and their characteristics can more readily facilitate concrete scholarly discussion concerning translingual writing instruction as it moves forward. I conclude with recommendations and cautions, bringing into question some of the settled assumptions remaining in our field.